Chair-side CAD/CAM fabrication of a single-retainer resin bonded fixed dental prosthesis: a case report - Jurado, Carlos Alberto (Restor Dent Endod, 2020)
This clinical report describes designing and fabricating a single-retainer resin-bonded fixed dental prosthesis with a chair-side computer-aided design/computer-aided manufacturing system. The whole procedure, from tooth extraction to final placement of the prosthesis, was completed in one day, and a single clinic visit. No clinical complications were found at the 2-year follow-up after placement of the restoration, and satisfactory functional and esthetic results were achieved.